Pengaruh Pengetahuan Perpajakan, Sanksi Perpajakan, dan Kualitas Pelayanan terhadap Keikutsertaan Program Tax Amnesty dengan Kondisi Keuangan sebagai Variabel Moderasi - Prastyatini, Sri Lestari Yuli; Putra, Weky Mandala Utama (Universitas Batanghari Jambi, 2024)
This study aims to prove the effect of taxation, tax sanctions, and service quality on participation in the tax amnesty program with financial condition as a moderating variable. This research is quantitative and primary data. Research time: This research was conducted from April to May 2023 with 105 respondents, namely taxpayers. This study uses Moderated Regression Analysis (MRA) where the results of the research show that knowledge of taxation does not affect participation in the tax amnesty program. Meanwhile, tax sanctions and service quality influence tax amnest participation. As well as financial conditions moderate the influence of tax knowledge on participation in tax amnesty while financial conditions do not moderate the effect of tax sanctions on participation in tax amnesty and financial conditions do not moderate the effect of service quality on participation in tax amnesty.